Seasonal variations and its impacts on livestock production systems with a special reference to dairy animals: An appraisal - Biswal, Jyotsnarani; Kennady, Vijayalakshmy; Rahman, Habibar (Bilingual Publishing Group, 2020)
Seasonal climatic variations is one of the most important environmental issues at present, the devastating impact of which is visualized on the ecology, ecosystem, and species survival. The livestock sector, which has been the source of animal protein for ever-increasing human masses, is subjected to the increased environmental temperature and higher frequency of extreme events. The impact of a high degree of heat stress is found to have a direct bearing on the milk production, growth, feed intake, reproductive efficiency, and disease incidence of the animals. The environmental temperature above the thermo-neutral zone of the animals has not only been adversely affecting the productivity and survival in the intensive livestock production systems, but the impact is equally seen in the extensive systems. Besides reduced milk production and change in composition, the impact of heat stress on dairy animals, in general, can be seen from the reduction of sperm quantity and quality in case of male and a marked decline in fertility and embryo quality in the case of females. The paper analyses varied aspects of climate change impacts on production, productivity, reproduction, and health of livestock, with a special focus on dairy animals.